232k views
1 vote
How do I substitute this?

How do I substitute this?-example-1
User Bakkot
by
5.0k points

1 Answer

2 votes

You want to isolate one of the variables (x or y) so you can plug it into the other equation. The easiest one is isolating the 2nd equation.

3x² - 16x + 13 - y = 0 Add y on both sides

3x² - 16x + 13 = y

You can use this and plug it into the first equation

y - 12x + 15 = 3x²

(3x² - 16x + 13) - 12x + 15 = 3x²

3x² - 16x + 13 - 12x + 15 = 3x² Combine like terms

3x² - 28x + 28 = 3x² Subtract 3x² on both sides

-28x + 28 = 0 Add 28x on both sides

28 = 28x Divide 28 on both sides

1 = x

Now that you know x, you can plug it into either of the equation to find y

3(1)² - 16(1) + 13 - y = 0

3 - 16 + 13 - y = 0

-y = 0 Divide -1 on both sides

y = 0


x = 1, y = 0

User Lethal
by
5.8k points